The interplay between assumed morphology and the direct radiative effect of light‐absorbing organic aerosol. Issue 16 (24th August 2016) - Saleh, Rawad; Adams, Peter J.; Donahue, Neil M.; Robinson, Allen L.
Abstract: Mie theory is widely employed in aerosol top‐of‐the‐atmosphere direct radiative effect (DRE) calculations and to retrieve the absorptivity of light‐absorbing organic aerosol (OA) from measurements. However, when OA is internally mixed with black carbon, it may exhibit complex morphologies whose optical behavior is imperfectly predicted by Mie theory, introducing bias in the retrieved absorptivities. We performed numerical experiments and global radiative transfer modeling (RTM) to investigate the effect of this bias on the calculated absorption and thus the DRE. We show that using true OA absorptivity, retrieved with a realistic representation of the complex morphology, leads to significant errors in DRE when the RTM employs the simplified Mie theory. On the other hand, when Mie theory is consistently applied in both OA absorptivity retrieval and the RTM, the errors largely cancel out, yielding accurate DRE. As long as global RTMs use Mie theory, they should implement parametrizations of light‐absorbing OA derived from retrievals based on Mie theory. Key Points: Assumed particle morphology affects the retrieval of light‐absorbing organic aerosol absorptivity Assumed morphology affects the direct radiative effect calculations in large‐scale models Consistency in the assumed morphology between retrievals and models is key